2020
DOI: 10.1097/acm.0000000000002991
|View full text |Cite
|
Sign up to set email alerts
|

Tensions in Assessment: The Realities of Entrustment in Internal Medicine

Abstract: Purpose A key unit of assessment in competency-based medical education (CBME) is the entrustable professional activity. The variations in how entrustment is perceived and enacted across specialties are not well understood. This study aimed to develop a thorough understanding of the process, concept, and language of entrustment as it pertains to internal medicine (IM). Method Attending supervisors of IM trainees on the clinical teaching unit were purposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Ideally, supervisors make entrustment decisions that grant a trainee an appropriate degree of independence to match their level of competence 3 . Yet, as educators apply the framework of entrustment, evidence of how entrustment‐based assessment provides trainees' guidance for achieving educational goals remains less clear 4–7 . Supervisors' feedback from entrustment‐granting clinical encounters may provide trainees with guidance on how to achieve higher entrustment, which may, in turn, capture trainees' learning needs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ideally, supervisors make entrustment decisions that grant a trainee an appropriate degree of independence to match their level of competence 3 . Yet, as educators apply the framework of entrustment, evidence of how entrustment‐based assessment provides trainees' guidance for achieving educational goals remains less clear 4–7 . Supervisors' feedback from entrustment‐granting clinical encounters may provide trainees with guidance on how to achieve higher entrustment, which may, in turn, capture trainees' learning needs.…”
Section: Introductionmentioning
confidence: 99%
“…3 Yet, as educators apply the framework of entrustment, evidence of how entrustment-based assessment provides trainees' guidance for achieving educational goals remains less clear. [4][5][6][7] Supervisors' feedback from entrustment-granting clinical encounters may provide trainees with guidance on how to achieve higher entrustment, which may, in turn, capture trainees' learning needs. This interaction between supervisors' entrustment decisions and trainees' learning needs has yet to be demonstrated empirically.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the use of entrustability scales in practice has been met with confusion, concern, and criticism. 4 Since then, ten Cate et al and others have suggested a number of refinements and corrections, including the need to disentangle ''retrospective'' and ''prospective'' assessments. [5][6][7] In this Perspectives article we pick up on this distinction between retrospective and prospective assessment using assessment validity as our framework and the O-SCORE as our example.…”
mentioning
confidence: 99%
“…A recent study by Melvin et al focusing on the tension and realities of entrustment suggested that it was important to understand the complexity and specialty-specific language of entrustment in order to provide effective assessments to learners. 35 Residents' perceptions that anything less than the highest rating was a "wasted EPA observation" highlighted an interesting disconnect around the programmatic assessment aspect of the core components framework. This highlights residents' perceptions that EPA assessments are solely a type of summative assessment, rather than having a largely formative purpose as they were intended, which has been echoed by other residents as well.…”
Section: Discussionmentioning
confidence: 99%